Biological effects of tolerable level chronic boron intake on transcription factors - Orenay Boyacioglu, Seda; Korkmaz, Mehmet; Kahraman, Erkan; Yildirim, Hatice; Bora, Selin; Ataman, Osman Yavuz (Journal of trace elements in medicine and biology, 2017)
The mechanism of boron effect on human transcription and translation has not been fully understood. In the current study it was aimed to reveal the role of boron on the expression of certain transcription factors that play key roles in many cellular pathways on human subjects chronically exposed to low amounts of boron. The boron concentrations in drinking water samples were 1.57±0.06mg/l for boron group while the corresponding value for the control group was 0.016±0.002mg/l. RNA isolation was performed using PAX gene RNA kit on the blood samples from the subjects. The RNA was then reverse transcribed into cDNA and analyzed using the Human Transcription Factors RT2 Profiler™ PCR Arrays. While the boron amount in urine was detected as 3.56±1.47mg/day in the boron group, it was 0.72±0.30mg/day in the control group. Daily boron intake of the boron and control groups were calculated to be 6.98±3.39 and 1.18±0.41mg/day, respectively. The expression levels of the transcription factor genes were compared between the boron and control groups and no statistically significant difference was detected (P>0.05). The data suggest that boron intake at 6.98±3.39mg/day, which is the dose at which beneficial effects might be seen, does not result in toxicity at molecular level since the expression levels of transcription factors are not changed. Although boron intake over this level will seem to increase RNA synthesis, further examination of the topic is needed using new molecular epidemiological data.